City deals and health equity in Sydney, Australia. (January 2022) - Harris, Patrick; Fisher, Matt; Friel, Sharon; Sainsbury, Peter; Harris, Elizabeth; De Leeuw, Evelyne; Baum, Fran
Abstract: 'City Deals' are new governance instruments for urban development. Vast evidence exists on the relationship between urban factors and health equity, but little research applies a health equity lens to urban policy-making. This paper does precisely that for the Western Sydney City Deal (WSCD) in Australia. We conducted a critical discourse analysis of publicly available documents and interviews with the WSCD's main architects, applying insights from relevant theories. We find 'pro-growth' discourse to encourage economic investment dominates any references to disadvantage. Interviewees maintained the WSCDs fundamental purpose is to rebalance urban investment toward the historically disadvantaged West. However, the WSCD makes limited reference to health and none to equity. Institutionalised governance practices that favour private investments in infrastructure remain the dominant force behind the WSCD. We document how a shift to 'place-based' infrastructure has promise for equity but struggles to overcome institutionalised approaches to urban investments. Highlights: City Deals are major urban policy initiatives with implications for health equity. WSCD's primarily concern is leveraging investment in a new airport for regional economic growth. WSCD's discourse emphasises economic strengths and avoids disadvantage. A shift to 'place-based' infrastructure opens up opportunities for equity. Institutionalised governance for economic investment undercuts local place-making.